Symptomatic vigabatrin‐associated MRI toxicity is associated with simultaneous hormonal therapy among patients with infantile spasms - Rujuta Sathe; Gyaneshwar Shrestha; Aria Terango; David Tabibzadeh; Rajsekar R. Rajaraman; Hiroki Nariai; Shaun A. Hussain (Epilepsia Open)
Abstract Vigabatrin‐associated brain abnormalities on MRI (VABAM) are observed in approximately 20% of children who receive vigabatrin for treatment of infantile epileptic spasms syndrome. Although usually reversible and asymptomatic, VABAM is occasionally symptomatic. Whereas asymptomatic VABAM appears to be dose‐dependent, symptomatic VABAM is possibly associated with co‐administration of vigabatrin and hormonal therapy (i.e., corticosteroids or adrenocorticotropic hormone). With retrospective study of a cohort of vigabatrin‐treated children, we evaluated candidate risk factors for VABAM. Among 108 children with detailed vigabatrin exposure data, we identified VABAM in 17 children (11 symptomatic). Symptomatic VABAM was strongly associated with simultaneous exposure to hormonal therapy (p = 0.001). Neither symptomatic nor asymptomatic VABAM were associated with peak vigabatrin dose. Although these data support the hypothesis that symptomatic VABAM risk is higher with coadministration of vigabatrin and hormonal therapy, this study does not establish a causal link. Further study is warranted to better understand the pathogenesis of VABAM and devise strategies to mitigate risk. Clinicians should carefully weigh the potential risk of symptomatic vigabatrin toxicity against the known benefit of vigabatrin and hormonal therapy coadministration. Plain Language Summary Several case reports suggest that the combination of vigabatrin and hormonal therapy for treatment of infantile spasms may provoke an adverse reaction known as symptomatic vigabatrin MRI toxicity (sVABAM, which includes characteristic changes on MRI images and associated symptoms). In response to these reports, we studied a large single‐center cohort of children with infantile spasms and determined that combination therapy is indeed statistically associated with sVABAM. However, we have not proven that combination therapy actually causes sVABAM. Further study is needed to clarify the nature of sVABAM and risk factors thereof.